Associations of exercise frequency and cardiorespiratory fitness with symptoms of depression and anxiety - a cross-sectional study of 36, 595 adults. (October 2020) - Hallgren, Mats; Kandola, Aaron; Stubbs, Brendon; Nguyen, Thi-Thuy-Dung; Wallin, Peter; Andersson, Gunnar; Ekblom-Bak, Elin
Abstract: Introduction: Regular exercise has been associated with better mental health, but relationships of cardiorespiratory fitness (CRF) with mental health symptoms are less certain. We conducted a large cross-sectional study to examine associations of exercise frequency and objectively measured CRF with symptoms of depression and anxiety. Methods: Data originates from the Swedish Health Profile Assessment (HPA) database, a general health assessment offered to all employees working for companies or organizations connected to occupational and health services. Participants reported the frequency (last 30 days) of structured exercise and completed a 6-min VO2max test on a cycle ergometer to determine CRF. Data on relevant covariates including leisure-time sedentary behavior were also collected. The study outcome was self-reported frequent (often/very often) symptoms of depression and anxiety. Results: Complete data from 36, 595 participants were analyzed (41% female, mean age = 42 years). In fully-adjusted models, compared to those in the lowest exercise frequency category (never/sometimes), those exercising 1–2 times/week and ≥3 times/week had 0.75 (95% CI = 0.68–0.82) and 0.72 (95% CI = 0.65–0.79) lower odds of reporting frequent symptoms of depression/anxiety, respectively. For CRF, crude models indicated a dose-response with the odds of frequent depression/anxiety symptoms reducing with higher CRF levels (low versus medium and high, respectively). No associations were found after adjustment for leisure-time sedentary behavior. Conclusions: Exercising at least 1–2 times per week is associated with lower odds of depression/anxiety symptoms. Leisure-time sedentary behavior attenuates relationships of CRF with depression/anxiety symptoms. Highlights: Exercising at least 1–2 times/week was associated with lower odds of depression/anxiety symptoms. In partly-adjusted models, higher cardiorespiratory fitness was associated with lower odds of depression/anxiety symptoms. No associations with fitness were seen after adjustment for leisure-time sedentary behavior.